Efektivitas Seduhan Zingiber Offcinale (Jahe) Dalam Mengatasi Mual Muntah pada Kehamilan Trimester 1 - Lola Pebrianthy; Nefonavratilonga Sitonga (Universitas Baiturrahim, 2021)
Nausea vomiting is one of the most common symptoms that can cause stress in pregnant women also cause nutritional disorders, dehydration, weakness, weight loss, as well as electrolyte imbalance in the mother's body which can have a negative impact on fetal development Common non-pharmacological actions are recommended such as consumption ginger in the form of ginger juice. The purpose of this study is to find out the difference in the frequency of nausea vomiting before and after being given ginger juice in the working area of Puskesmas Batunadua Kota Padangsidimpuan in 2019. This study is a pre-experiment with a design used is a group pretest-postest design with a sample of 18 people. This study used a paired sample T-Test with a result of p = 0.012 (p <0.05) with an average frequency of nausea vomiting before being given ginger is 8,83 and the average frequency of nausea vomiting after being given ginger is 7,50. The conclusion of this study is that the frequency of nausea and vomiting of pregnant women decreases after intervention, in this case it means that ginger ale is effective in reducing nausea in pregnancy in trimester 1. It is recommended that pregnant women want to consume ginger juice if they experience nausea during pregnancy trimester I.